2020
DOI: 10.3390/ijms21249684
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Dental Materials Used in Conservative Dentistry, Endodontics, Surgery, and Orthodontics as Well as during the Periodontal Treatment on the Redox Balance in the Oral Cavity

Abstract: Oxidative stress (OS) is a redox homeostasis disorder that results in oxidation of cell components and thus disturbs cell metabolism. OS is induced by numerous internal as well as external factors. According to recent studies, dental treatment may also be one of them. The aim of our work was to assess the effect of dental treatment on the redox balance of the oral cavity. We reviewed literature available in PubMed, Medline, and Scopus databases, including the results from 2010 to 2020. Publications were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 128 publications
0
31
0
1
Order By: Relevance
“…This suggests a negligible effect of salivary hypofunction on salivary TNF-α, IL-6, and IL-10 levels. Nevertheless, aging, medications, diet supplements, smoking, as well as oral and systemic diseases can also modify the cytokine profile of saliva 89 91 . At this time, it is important to emphasize the careful selection of the control group in the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a negligible effect of salivary hypofunction on salivary TNF-α, IL-6, and IL-10 levels. Nevertheless, aging, medications, diet supplements, smoking, as well as oral and systemic diseases can also modify the cytokine profile of saliva 89 91 . At this time, it is important to emphasize the careful selection of the control group in the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the results obtained in plasma and red cell lysate revealed a signi cant decrease in SOD and GPx activity (∃17%, ∃39%, respectively), increase in CAT activity (#17%), decrease in the concentration of non-enzymatic antioxidants (∃38% UA, ∃25% GSH, ∃39% TAC) and the existence of general OS (#95% TOS, #227% OSI, #26% MDA, #47% AGE, #42% AOPP) and nitrosative stress (#4% peroxynitrite, #94% nitrotyrosine). TAC is the resultant capacity of a given biological material to counteract speci c oxidation reactions 32 . It is believed that TAC level corresponds to the antioxidant capacity of non-enzymatic antioxidants in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes (salivary peroxidase system (Px), lactoperoxidase, myeloperoxidase (MPO), glutathione peroxidase (GPx), or catalase (CAT)) as well as low molecular weight nonenzymatic antioxidants (uric acid (UA), reduced glutathione (GSH), albumin, or vitamin C) are the first line of defense against oxygen free radicals [ 62 64 ]. The oral cavity is the only place in the body that is exposed to so many environmental factors such as air pollutants, xenobiotics, stimulants, or dental materials/treatments [ 65 67 ]. Although many external factors can affect the redox homeostasis of saliva, its composition is not significantly different from blood serum and plasma [ 68 70 ].…”
Section: Saliva As a Source Of Redox And Inflammatory Biomarkersmentioning
confidence: 99%
“…Interestingly, it has been shown that dental treatment, as well as materials used, different xenobiotics, e.g., tobacco use, ethanol or drugs, physical exercises, and food (i.e., chronic high-fat/high-carbohydrate/high-protein diet) may induce oxidative stress [ 65 67 , 165 , 210 ]. Needless to say, the oral cavity is a unique part of the body subjected to numerous environmental factors.…”
Section: Limitations Of Salivary Redox and Inflammatory Biomarkersmentioning
confidence: 99%